Antecedents of voluntary pro-environmental behavior among textile industry employees in Pakistan - Zafar, Hina (2023)
The Pakistani textile industry is a major contributor to pollution in the country, which underscores the urgent need for it to shift towards environmental sustainability. Based on the theories of social exchange and social identity, this research investigated how perceptions of organizational and colleague support towards the environment, environmentally specific servant leadership, and green human resource management (GHRM) practices affect the voluntary pro-environmental behavior (VPEB) of employees in the Pakistani textile industry. This study also tested the mediating role of organizational identity in the influence of green climate on employees’ VPEB. Additionally, the moderating role of psychological empowerment in the perceived organizational support towards environment- environmentally specific servant leadership relationship, as well as in the impact of green climate on organizational identity, was examined. To collect data, a survey questionnaire was administered to 459 employees and 109 managers at two time points. The results from the SmartPLS analysis indicated that perceived organizational support towards environment, environmentally specific servant leadership, perceived colleague support towards environment, and GHRM practices significantly influence employees’ VPEB. This confirms the principles of the Social Exchange Theory which posits that positive actions (like organizational support) lead to reciprocated positive behaviors (like employees' VPEB). This study also found that organizational identity mediated the impact of green climate on VPEB. The study enriches the Social Identity Theory by demonstrating that a green climate can foster an organizational identity among employees. This, in turn, boosts their engagement in carrying out VPEB. Therefore, developing practices that cultivate an organization’s green climate is essential. The results further verified the moderating effect of psychological empowerment on the link between green climate and organizational identity. Thus, the results reaffirm the principles of the Social Exchange Theory, highlighting the nuanced role of psychological empowerment as a moderating force that bridges the connection between a green climate and organizational identity. However, psychological empowerment failed to exhibit a significant moderating influence on the impacts of the perceived organizational support towards environment- environmentally specific servant leadership relationship. This research’s findings have identified key antecedents, underlying mechanisms, and conditional effects pertaining to VPEB. In doing so, this study not only broadens the VPEB literature, but also contributes to research on GHRM and psychological empowerment.